The knife cuts on both sides: Examining the relationship between cross‐domain communication and work–family interface. Issue 4 (7th August 2019) - Wan, Min (Maggie); Shaffer, Margaret A.; Lau, Theresa; Cheung, Eric
Abstract : Our study aimed to understand how cross‐domain communication via technology affects employees' work–family interface. We examine the relationships among cross‐domain communication, role‐based resource loss and gain, and the bidirectional forms of work–family conflict and enrichment. Building on Conservation of Resources theory, we expect that cross‐domain communication has positive effects on role‐based resource loss and gain as well as both work–family conflict and enrichment. Furthermore, we suggest that the relationships between cross‐domain communication and role‐based resource loss and gain vary across different levels of role response expectations and role relationship quality. We test our ideas with data from two studies. Results confirm the role of cross‐domain communication on work–family conflict and enrichment through role‐based resource loss and gain. We also find significant interactions involving cross‐domain communication, role response expectations, and role relationship quality on both work‐ and family‐based resource loss and gain as well as on the mediating effects of family‐based resource loss. Practitioner points: Cross‐domain work and family communication is not always harmful to employees' work and family interface. When employees engaged in cross‐domain communication perceive high work (family) response expectations and high‐quality work (family) relationships, they experience more personal resource losses and gains within the family (work) domain. Managers need to educate employees regarding both the pros and cons of cross‐domain work and family communication and provide them with explicit rules about how they can navigate the double‐edged functions of communicating across work and family domains. Training employees to manage communications across domains will enable them to reduce potential work–family conflict and enhance work–family enrichment.